Knowledge, Attitude and Practice towards Covid-19 in Different Universities across Khyber Pakhtunkhwa, Pakistan: Knowledge, Attitude, and Practice towards Covid-19 - Tahir Usman,; Khattak, Irfan; Mustafa Kamal,; Arsalan Rasheed,; Johar Ali,; Naimat Ullah Khan,; Adnan Khan,; Ibrar Muhammad Khan,; Samad, Abdul; Anwer Hussain,; Ali, Tariq (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
There have been 6,566,610 fatalities and 626,337,158 reported cases of COVID-19 worldwide. Pakistan presently has over 1,573,922 confirmed cases and 30,625 deaths. A survey-based study was performed from January to September 2022 among different university communities to find out their KAP level. Data was collected in Google Forms through a questionnaire. The Independent t-test, Multinomial regressions, and Non-parametric Mann-Whitney test were used to assess the level of significance (p-value ≤0.05). 317 out of 605 participants were male (52.5 %), the majority of participants were 15-29 years old (72.7 %), unmarried/divorced (71.6 %), have no children (82.1 %), residing in the urban area (54.9 %) and possess a college/university degree (59.5 %). The majority of participants correctly answered five out of six knowledge questions (M = 4.96, SD = 1.03) and correctly identified the primary symptoms of COVID-19 (94.4 %) along with the proper identification of mode of transmission (95.2 %) while 1.8% wrongly replied and 2.1 % did not reply. A knowledge test revealed the significant frequency of misconception, with nearly half of the respondents (46.3 %) assuming that illness might be contracted by eating or coming into touch with wild animals. Wearing a facial mask is highly practiced (M = 3.59, SD = 0.91), followed by avoiding crowded places (M = 3.44, SD = 0.95) and practicing hand hygiene (M = 3.36, SD = 1.04). Females, the elderly, and the less educated, on the other hand, have less understanding of COVID-19, making them especially susceptible to the pandemic. It is proposed that further awareness might contribute to a favorable attitude and practice.